Histologic Grading of Canine Mast Cell Tumor: Is 2 Better Than 3?. (January 2015) - Sabattini, S.; Scarpa, F.; Berlato, D.; Bettini, G.
Mast cell tumor (MCT) is a common canine cutaneous neoplasm with variable biological behavior. A 2-tier histologic grading system was recently proposed by Kiupel et al to reduce interobserver variation and eliminate prognostic uncertainty of the Patnaik system. This study compared the ability of these 2 grading systems to predict survival in a cohort of dogs with MCTs. However, surgical margins were unknown, and the risk of developing new/metastatic MCTs was not studied. Histologic grade was assessed according to both systems for 137 surgically resected cutaneous MCTs. The relationship between grade and survival was evaluated. According to the Patnaik system, 18 MCTs (13.1%) were classified as grade I, 83 (60.6%) as grade II, and 36 (26.3%) as grade III. Grade III was associated with a poorer prognosis ( P < .001), but no significant difference between grades I and II was detected. Grading according to the Patnaik system was based on consensus grading among 3 pathologists, and interobserver variability was not considered. All grade I MCTs were low grade in the Kiupel system, and all grade III were high grade. Among grade II, 71 (85.6%) were low grade, and 12 (14.4%) were high grade, with a 1-year survival probability of 94% and 46%, respectively ( P < .001). The 2-tier system had a high prognostic value and was able to correctly predict the negative outcomes of some grade II MCTs. Data also confirm that histologic grading cannot predict biological behavior of each MCT and should be supplemented with molecular methods for more accurate prognostication.